A Study of Intrinsic and Extrinsic Factors Influencing Consumer Buying Behaviour Online. (March 2013) - Bagga, Teena; Bhatt, Manas
The purpose of this article is to identify the various intrinsic and extrinsic factors which effect the consumer's buying behaviour online. The intrinsic factors are the inner motivations or drives of the consumers and the extrinsic factors are the marketer generated Internet marketing activities. The article aims at identifying these factors and their relative importance on the consumer's purchase behaviour. The theoretical framework of this article is based on a vast Internet marketing literature. The hypothesised model was created that took into account the dependent and independent variables which were extracted using an exploratory factor analysis and these variables were used to construct hypotheses which were empirically tested through techniques such as independent t -tests and ANOVA. A structured questionnaire was used for this purpose and a survey was conducted on a sample of 200 through judgemental sampling. Questionnaires were filled by respondents in person as well as a pre-defined list of respondents based on their demographic profile was selected and questionnaires were mailed and posted online. The Exploratory Factor Analysis identified seven major intrinsic and extrinsic factors which govern the consumer's buying behaviour. These seven factors were: Need for Recreation, Convenience, Website Attributes, Online Advertising, Social Communication, Information Search and Security and privacy concerns. The importance of these seven factors differ across different demographic variables such as age, income group of consumers and gender. The article presents a simple approach towards identifying the most effective Internet marketing tools that companies should employ and also helps in better understanding the online consumer behaviour which differs from the traditional consumer behaviour across various dimensions.